The Effect of Word Wall Media on Young Learners’ English Vocabulary Mastery - Arta, Sarah; Mafulah, Siti; Herawati, Siane (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The purpose of this research is to explore the differences in vocabulary mastery between students given Word Wall media and students given book learning media in vocabulary mastery among grade 2 students at SD Negeri 1 Kalipare in the even semester of the 2024/2025 school year. This research was carried out over six meetings using a Quasi-Experimental research design and quantitative methods. The participants involved in this study consisted of two classes with 42 students. And twenty-one students per class. The research employed pre-test and post-test data collection techniques. The post-test result indicates that the vocabulary proficiency of students in the experimental class is 75.00 at the same times as in the control class which is 55.476. So, student learning outcomes on vocabulary mastery related to family members and possessive adjectives through using Word Wall media in grade 2 students of SDN Kalipare 1 increased. The results indicate that Word Wall media can effectively enhance students’ vocabulary achievement.